The Effect of Free Androgen Index on the Quality of Life of Women With Polycystic Ovary Syndrome: A Cross-Sectional Study - Abdalla, Mohammed Altigani; Deshmukh, Harshal; Mohammed, Irfaan; Atkin, Stephen; Reid, Marie; Sathyapalan, Thozhukat (Frontiers in Physiology, 2021)
Abstract Purpose: Free androgen index (FAI) and anti-Mullerian hormone (AMH) are independently associated with polycystic ovary syndrome (PCOS). This study aimed to describe the relationship between these two markers and health-related quality of life (HR-QoL) in women with PCOS. Methods: This cross-sectional study consisted of 81 women in the Hull PCOS biobank, who fulfilled the Rotterdam consensus criteria for the diagnosis of PCOS. The primary outcome was to measure the various domains of the QoL in the modified polycystic ovary syndrome questionnaire (MPCOSQ). Results: Mean age of the study participants was 28 ± 6.0 years, mean body mass index (BMI) 33.5 ± 7.8 kg/m2, mean FAI 6 ± 5.5 and mean AMH 3.5±0.8 (units). In linear regression analysis, the FAI was associated with overall mean MPCOSQ score (Beta=0.53, P-value= 0.0002), and with depression (Beta=0.45, P-value=0.01), hirsutism (Beta=0.99, P-value=0.0002) and menstrual irregularity (Beta=0.31 , P-value= 0.04). However, with adjustment for age and BMI, FAI was only associated with the hirsutism domain (Beta=0.94, P-value=0.001) of the modified PCOS questionnaire (MPCOSQ). FAI was also associated with the weight domain (Beta=0.63 P-value=0.005) of MPCOSQ. However, AMH was not associated with the overall mean MPCOSQ score or with any of its domains. Conclusions: FAI but not AMH was associated with QoL in women with PCOS, and this effect was mediated by BMI. Keywords: Polycystic ovary syndrome - Quality of life (QoL) - Modified PCOS Questionnaire (MPCOSQ) - Anti-Mullerian hormone (AMH) - Free androgen index (FAI).